NCTF-FL Controller for Pendulum Balancing System - Noor Hisham Jalani (Institute of Advanced Engineering and Science, 2015)
Pendulum Balancing of Linear Servo System consists of a cart driven by a DC motor, via a rack and pinion mechanism to ensure consistent and continuous traction. The cart is also equipped with a rotary joint to which a free turning rod (or pendulum) can be attached. This concept paper proposed a combination of Nominal Characteristic Trajectory Following (NCTF) and Fuzzy Logic (FL) to control the position of the cart and to balance the pendulum. The proposed controllers are expected to have a simple design method and achieved high performances.